2013
DOI: 10.1136/thoraxjnl-2012-203178
|View full text |Cite
|
Sign up to set email alerts
|

Metformin reduces airway glucose permeability and hyperglycaemia-inducedStaphylococcus aureusload independently of effects on blood glucose

Abstract: BackgroundDiabetes is a risk factor for respiratory infection, and hyperglycaemia is associated with increased glucose in airway surface liquid and risk of Staphylococcus aureus infection.ObjectivesTo investigate whether elevation of basolateral/blood glucose concentration promotes airway Staphylococcus aureus growth and whether pretreatment with the antidiabetic drug metformin affects this relationship.MethodsHuman airway epithelial cells grown at air–liquid interface (±18 h pre-treatment, 30 μM–1 mM metformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 38 publications
7
91
0
Order By: Relevance
“…In doing so, this work has revealed an elusive link between the stress-sensing components and the cell polarity pathways (see legend, Figure 10), and improved our understanding of molecular mechanisms of how epithelial monolayers are protected despite being constantly bombarded by energetic stressors by fortifying cell-cell junctions against stress-induced collapse. Because GIV serves as a junctional scaffold in both epithelial (Sasaki et al, 2015) and endothelial cells (Ichimiya et al, 2015), it is possible that the stress-triggered mechanisms outlined here also account for the protective role of AMPK on cell junctions observed consistently in a variety of tissue and cell types, in both epithelial (Garnett et al, 2013; Patkee et al, 2016; Seo-Mayer et al, 2011; Spruss et al, 2012) and endothelial (Castanares-Zapatero et al, 2013; Liu et al, 2014; Takata et al, 2013) cells, in the face of diverse chemical, bacterial and metabolic stressors. Given the overlapping substrate specificity of AMPK and its related kinases [reviewed in (Shackelford and Shaw, 2009)], it seems likely that AMPK-related family members such as the MARKs, may phosphorylate S245 on GIV under other conditions or in specific tissues.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In doing so, this work has revealed an elusive link between the stress-sensing components and the cell polarity pathways (see legend, Figure 10), and improved our understanding of molecular mechanisms of how epithelial monolayers are protected despite being constantly bombarded by energetic stressors by fortifying cell-cell junctions against stress-induced collapse. Because GIV serves as a junctional scaffold in both epithelial (Sasaki et al, 2015) and endothelial cells (Ichimiya et al, 2015), it is possible that the stress-triggered mechanisms outlined here also account for the protective role of AMPK on cell junctions observed consistently in a variety of tissue and cell types, in both epithelial (Garnett et al, 2013; Patkee et al, 2016; Seo-Mayer et al, 2011; Spruss et al, 2012) and endothelial (Castanares-Zapatero et al, 2013; Liu et al, 2014; Takata et al, 2013) cells, in the face of diverse chemical, bacterial and metabolic stressors. Given the overlapping substrate specificity of AMPK and its related kinases [reviewed in (Shackelford and Shaw, 2009)], it seems likely that AMPK-related family members such as the MARKs, may phosphorylate S245 on GIV under other conditions or in specific tissues.…”
Section: Resultsmentioning
confidence: 97%
“…Together, these discoveries established the first links between energetic stress, cell polarity and oncogenesis. Since then, multiple studies have reported the protective role of AMPK in maintaining cell-cell junctions across a variety of cell types in diverse tissue types [lung (Garnett et al, 2013), heart (Castanares-Zapatero et al, 2013), the blood-brain barrier (Liu et al, 2014; Takata et al, 2013), kidney (Seo-Mayer et al, 2011), intestine (Spruss et al, 2012)] while mounting a pathologic response to a variety of stressors, from bacterial invasion (Patkee et al, 2016) to ischemia (Seo-Mayer et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…in diabetes mellitus) and, more potently, when both are present. Similar changes can also be detected in the ASL of in vitro models of airway epithelium in response to basolateral hyperglycaemia and pro-inflammatory stimuli [57]. The increase in ASL glucose concentrations makes the airways more susceptible to infection from pathogens such as methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa .…”
Section: Introductionmentioning
confidence: 80%
“…8 Limited epidemiological data are available comparing the association of different GLDs with risk of infections. 6 9 In a Swedish study based on 51 675 patients with type 2 diabetes treated Strengths and limitations of this study ▪ Large nationwide population-based study based on prospectively collected data from hospitals and general practices.…”
Section: Introductionmentioning
confidence: 99%